The Use of Technology in Nursing: A Grounded Theory for Getting a Picture - Nagel, Daniel (Université d'Ottawa / University of Ottawa, 2017)
Background: Using technology requires nurses to capture, retrieve and organize digital data within virtual environments. Nurses often integrate digital data with other data sources when providing patient care with telehealth technologies and conducting research. Little is understood of how nurses navigate technology and process digital data in professional practice. Purpose: The overall aim of this dissertation was to explore how nurses navigate virtual environments and integrate digital data in professional practice through a grounded theory study of how nurses know the person using telehealth technology. The goals of the dissertation were to: a) Describe how knowing the person occurs with use of telehealth technology; b) Create a theoretical conceptualization of how the nurse comes to know the person in a virtual environment; and, c) Explicate data collection and analytical processes in Charmaz’s constructivist grounded theory. Methods Charmaz’s constructivist grounded theory (ConGT) was used for the research study. Findings: The process of conducting this study yielded two outcomes: 1. A grounded theory and conceptualization for Getting a Picture, which illuminates an integrated and iterative interplay of seven processes and 21 sub-processes that nurses described when forming a mental image of the person being cared for. Twenty-two registered nurses from five telehealth programs in two different provincial health systems participated. Primary data sources included 22 first interviews and 11 second interviews with the participants, and five observational experiences. 2. The approach for conducting ConGT involved operationalizing a series of five steps in the analytic process to visualize and conceptualize Getting a Picture. These steps included Initial Data Collection, Initial Coding, Focused Coding, Theoretical Coding and Theory Building. Conclusion: Visualization played an instrumental role when technology was used for both knowing the person in a virtual environment and operationalizing the methodological processes for this ConGT research study. Three main themes related to this overall finding in this dissertation were: (a) visualization and conceptualization to create a mental image is evident in both clinical and research domains of nursing practice; (b) interoperability of technology can impact visualization; and (c) competencies are required to support mental imaging and use of technology in visualizing a whole and accurate picture.
Keywords: grounded theory; telehealth; constructivist; nursing; qualitative; technology